The employee's satisfaction toward the training programmes in Sabah Electricity Sdn Bhd / Ratna Rahim - Rahim, Ratna (2008)
This research is investigating the level of employee's satisfaction toward the training programmes in Sabah Electricity Sdn.Bhd. The objective of this research is to examine the factors associated with employee's satisfaction toward training programmes, to identify the most important training programs in SESB, to identify the level of satisfaction among SESB employees towards their training programs and to come out with opinion or recommendation on overall training programmes in SESB. The measurement test that been use in this research is frequency test and Spearman Correlation test. The findings in this research shows that the employees is highly satisfied with the training programmes that been provided in SESB. Even though the employees is satisfied with the training programmes that they had receive but there is some area that SESB should cope with.